STUDI KEAMANAN NASIONAL DALAM PRESPEKTIF DIPLOMASI PERTAHANAN INDONESIA - Soegeng, Soegeng (Universitas Perrtahanan Indonesia (UNHAN), 2020)
In this journal, the authors discuss the concept of national security studies andIndonesian Defense Diplomacy. Previous studies have not used much of the theory ofIndonesian Defense Diplomacy and the concept of national security studies to analyze it.Furthermore, this study aims to clarify national security studies from the perspective ofIndonesian Defense Diplomacy in producing defense policy. Through the contentanalysis approach method, the research results show the importance of strengtheningregulation and strengthening public diplomacy and military diplomacy to strengthendefense diplomacy. As stated in the 2015 Indonesian Defense White Paper, capacitybuilding and trust-building are intended to improve human resources for the Ministryof Defense and the TNI. The 2021 Draft State Budget aimed at accelerating the nationaleconomic recovery. Trust building aims to increase the trust of Indonesian DefenseDiplomacy with regional countries, for example, Russia and South Korea, Turkey. Theywere enhancing national security through economic strength, military and diplomacycapabilities, and conducting broader cooperation in the future. The strong economic,military, and Defense Diplomacy of Indonesia are the basis for strengthening NationalSecurity. In the future, it can face AGHT in this era of globalization.Keywords: Study concept, national security, Indonesian Defense Diplomacy